Diseño de un centro de procesamiento agroindustrial y carácter del paisaje rural, comunidad Zuleta, parroquia de Angochagua - Catucuago Caiza, Augusto Napoleón (2024)
The work is carried out in a rural area of Ibarra where the presence of corn and barley crops predominates, however, its natural, cultural and agricultural potential, although it has a great impact on its population and is a fundamental part of the development of its inhabitants, has not been studied in depth, representing a problem for a landscape as important as that of Zuleta. This rural area has great landscape potential, so it is necessary to analyze the factors that allow making the best decisions to design low-impact agro-industrial equipment, to improve the conditions of Zuleta with an agro-industrial architectural design that integrates characteristic aspects of the area. To do so, a mixed approach is used, which analyzes and evaluates the character of the landscape, in addition to addressing problems and needs of the population with focused tools such as: registration forms and kobotoolbox, respectively. These lead to obtaining criteria and conditions for the architectural proposal based on three fundamental points: productive diversity, rural landscape and industrialization of raw materials. Finally, the project concludes with a proposal for the design of a low-impact agro-industrial facility with complementary areas such as storage, training and marketing, which adapt to and take advantage of the potential of the context. The creation of an agro-industrial facility in a community has the potential to significantly transform the local economy by creating new forms of marketing, and can open up new markets and business opportunities for local farmers.